Synaptic Gain-of-Function Effects of Mutant Cav2.1 Channels in a Mouse Model of Familial Hemiplegic Migraine Are Due to Increased Basal [Ca2+]i - Di Guilmi, Mariano Nicolás (2014)
Specific missense mutations in the CACNA1A gene, which encodes a subunit of voltage-gated CaV2.1 channels, are associated with familial hemiplegic migraine type 1 (FHM1), a rare monogenic subtype of common migraine with aura. We used transgenic knock-in (KI) mice harboring the human pathogenic FHM1 mutation S218L to study presynaptic Ca2+ currents, EPSCs, and in vivo activity at the calyx of Held synapse. Whole-cell patch-clamp recordings of presynaptic terminals from S218L KI mice showed a strong shift of the calcium current I–V curve to more negative potentials, leading to an increase in basal [Ca2+]i, increased levels of spontaneous transmitter release, faster recovery from synaptic depression, and enhanced synaptic strength despite smaller action-potential-elicited Ca2+ currents. The gain-of-function of transmitter release of the S218L mutant was reproduced in vivo, including evidence for an increased release probability, demonstrating its relevance for glutamatergic transmission. This synaptic phenotype may explain the misbalance between excitation and inhibition in neuronal circuits resulting in a persistent hyperexcitability state and other migraine-relevant mechanisms such as an increased susceptibility to cortical spreading depression.